Analysis of the Role of Regional Autonomy on the Existence of Customary Land under Agrarian Law in Indonesia - Lubis, Mhd Azmi Farid Lubis (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
Regional autonomy grants local governments greater authority in managing natural resources, including land. This raises the question of the role of regional autonomy in preserving the existence of customary land, which often faces challenges in terms of protection and recognition of its rights amidst rapid development and national land policies. The main objective of this analysis is to examine the role of regional autonomy in the existence of customary land and the legal implications of recognition by local governments regarding customary land existence through regional regulations. The approach used in this research is a normative juridical approach, with secondary materials as the primary source. Regional autonomy plays a crucial role in maintaining the existence of customary land through recognition, inventory, and identification of customary land rights, as well as protecting, receiving aspirations, and processing complaints or legal actions related to violations of these rights. Recognition by local governments of the existence of customary land through regional regulations can strengthen the position of customary law, prevent conflicts, increase awareness and participation of indigenous communities, and provide legal protection for their rights to customary land.